A new forest-dwelling Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodactylus) from Doi Inthanon, Chiang Mai Province, northern Thailand - Kunya, Kirati; Sumontha, Montri; Panitvong, Nonn; Dongkumfu, Wuttipong; Sirisamphan, Thana; Pauwels, Olivier S. G. (Zootaxa, 2015)
We describe a new forest-dwelling Cyrtodactylus from Doi Inthanon, Chiang Mai Province, northern Thailand. Cyrtodactylus inthanon sp. nov. is characterized by a maximum known SVL of 87.3 mm; 18 to 20 longitudinal rows of dorsal tubercles; a continuous series of 34 to 37 enlarged femoro-precloacal scales, including four to six pitted (female) or pore-bearing (male) scales on each femur separated by a diastema from five pitted (females) or pore-bearing (male) precloacal scales; no precloacal groove or depression; transversely enlarged subcaudal scales; and three to five irregular beige dorsal bands between limb insertions. The discovery of a new reptile endemic to Doi Inthanon reinforces the high importance of this mountain in terms of biodiversity conservation.